Do-It-Yourself Interface Device Prototyping for Virtual Reality - Wins, Peter; Basu, Aryabrata; Johnsen, Kyle (International Journal of Virtual Reality, 2012)
the off-the-shelf virtual reality community is well aware of the wide variety of inexpensive and robust tracking and display technologies that have emerged from the entertainment industry in recent years. Alongside these developments, there has also been a vast improvement in the accessibility and usability of hobbyist-grade electronics components, which make incorporating lower-level sensing and actuation components into virtual reality systems feasible for even novices in electronics. Combined, these developments have formed the foundation for a renaissance of do-it-yourself interface device prototyping. Development of novel virtual reality interface devices has been simplified to the point that it can be commonplace in virtual reality system design, rather than an exception. This article discusses a variety of ways in which off-the-shelf electronics and devices can be leveraged and combined in virtual reality experiences, and the knowledge required to begin exploring possibilities, through case studies in prototyping virtual reality experiences.